The impact of bad debts on the resources of the Iraqi banking system (case study of the Iraqi banking system for the period from (2010-2015) - Jarallah, Sina Ahmed; Najim, Asmaa Suhail (International Journal of Psychosocial Rehabilitation, 2020)
The Iraqi banking system faced the problem of bad debts due to economic and administrative reasons. Whereas, banks with administrative and financial efficiency apply an approach in which credit risk is measured, including controls for customer study and selection criteria, in order to ensure pre-return financing. The importance of research is that non-performing debts lead to the freezing of a large part of the banks ’resources, as this reduces the rate of money circulation in the banking system and hence the lack of operational capacity for its resources, in addition to the social effects of non-performing clients. The research dealt with this phenomenon in three sections. The first topic reviewed the research methodology. As for the second topic, it included bad debts of their causes and how to early warning these debts, as well as the stages and types of these debts and their effects and methods of dealing with them. As for the third topic, it included the applied side that included a sample of bank employees The number of 45 employees and the analysis of this questionnaire using the spss program and to validate the hypotheses, and the most important results are that there are factors that lead to debt failure in Iraqi banks, where the total score of the factors determining the loan default in the research sample reached according to financial policies The bank has 61%, and it was the highest result, and the total score of attitudes related to the behavior of the customer reached 39%, and it was the second rank. The financial decision-making process, especially credit decisions, needs to be studied and analyzed in full to make the risks at a minimum, and whenever the early detection Debt faltering whenever it helps reduce its consequences.